Polar Vortex Conditions During the 1995-96 Arctic Winter: MLS CL0 and HNO 3 - Santee, M. L.; Manney, G. L.; Read, W. G.; Froidevaux, L.; Waters, J. W. (2004)
Microwave Limb Sounder (MLS) measurements of lower stratospheric CLO and HNO 3 during the 1995-96 Arctic winter are presented. The 1995-96 Arctic winter was both colder and more persistently cold than usual, leading to an enhancement in lower stratospheric CLO of greater magnitude, vertical extent, and duration than has been previously observed in the Arctic. Vortex concentrations of HNO 3 in mid-December were large due to diabetic decent. Trajectory calculations indicate that localized severe depletions of gas-phase HNO 3 in mid-February and early March did not arise from intrainment of midlatitude air into the vortex and were therefore probably related to polar stratospheric cloud (PSC) formation.